2022
DOI: 10.2147/ijgm.s349723
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Expression and Clinical Significance of E2F Family in Clear Cell Renal Cell Carcinoma

Abstract: Background: Multiple studies have identified that E2F transcriptions act as important regulators for the tumorigenesis and progression of several human cancers. However, little is known about the function of E2Fs in clear cell renal cell carcinoma (ccRCC). Methods: We firstly investigated the expression levels, genetic alteration, and biological function of E2Fs in patients with ccRCC and the connections between the immune cell infiltration and the overall survivals of ccRCC patients with the E2Fs expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In the KEGG pathway analyses, eight coding RNAs of the cell cycle and seven RNAs involved in cellular senescence were identified as probably the key‐coding RNAs involved in significantly heightening the malignant potential of vimentin‐positive IBC‐NSTs. Among these, since MYC, CDK6 , and E2F3 which were significantly upregulated are involved in both the cell cycle and cellular senescence pathways, these coding RNAs are probably especially closely involved in heightening the malignant potential of vimentin‐positive IBC‐NSTs 37–39 . Thirteen GO terms consisted of many important coding RNAs that could play very important roles in heightening the malignant potential of vimentin‐positive IBC‐NSTs; among these, the 12 coding RNAs that were significantly upregulated in three or more GO terms may be especially important coding RNAs (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the KEGG pathway analyses, eight coding RNAs of the cell cycle and seven RNAs involved in cellular senescence were identified as probably the key‐coding RNAs involved in significantly heightening the malignant potential of vimentin‐positive IBC‐NSTs. Among these, since MYC, CDK6 , and E2F3 which were significantly upregulated are involved in both the cell cycle and cellular senescence pathways, these coding RNAs are probably especially closely involved in heightening the malignant potential of vimentin‐positive IBC‐NSTs 37–39 . Thirteen GO terms consisted of many important coding RNAs that could play very important roles in heightening the malignant potential of vimentin‐positive IBC‐NSTs; among these, the 12 coding RNAs that were significantly upregulated in three or more GO terms may be especially important coding RNAs (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, since MYC, CDK6, and E2F3 which were significantly upregulated are involved in both the cell cycle and cellular senescence pathways, these coding RNAs are probably especially closely involved in heightening the malignant potential of vimentinpositive IBC-NSTs. [37][38][39] Thirteen GO terms consisted of many important coding RNAs that could play very important roles in heightening the malignant potential of vimentin-positive IBC-NSTs; among these, the 12 coding RNAs that were significantly upregulated in three or more GO terms may be especially important coding RNAs (Table 4). [40][41][42][43][44][45][46][47][48][49][50][51] This study clearly demonstrated a higher Ki67 labeling index of vimentin-positive IBC-NSTs than that of vimentin-negative IBC-NSTs; since all of the 12 coding RNAs play important roles in…”
Section: Mitotic Cytokinesismentioning
confidence: 99%
“…In order to assess relative gene expression, the 2 -ΔΔCq method was used. Additionally, the GAPDH gene was used as a reference gene and each of the analyses was performed in triplicate (22).…”
Section: Methodsmentioning
confidence: 99%